GERAKAN KAUM PADRI DI SUMATERA BARAT DAN PENGARUHNYA TERHADAP PEMBAHARUAN PEMIKIRAN ISLAM - Ibnu Ali; Mujiburrahman Mujiburrahman (Fakultas Agama Islam Universitas Islam Madura, 2023)
The 19th century AD was the beginning of the rise of the modern Islamic movement in Indonesia. One of them is the movement of the Padri in West Sumatra which has had a lot of influence on Islamic renewal in Indonesia, especially in West Sumatra. The research method in this study used a literature review or library research approach and the sources of research were several libraries that the researcher considered had a relationship with the research theme which was then reduced so that they became a feasible research source. The findings of this study are that Islamic teachings in Indonesia brought by Islamic propagators have taken the form of doctrines that are exclusive to one school of thought, and most of them adhere to the Shafi'i school of fiqh, and Asy'ariyah in theology. On the other hand, traditions passed down from previous ancestors who were born from Hindu-Buddhist teachings still dominate strongly in people's lives. So this paper analyzes the Padri starting from their movements and reforming ideas in the midst of this social context. The implications of the research show that people come to understand that the Padri movement has made a positive contribution to the renewal of Islamic thought in Indonesia, more specifically in West Sumatra.